Fall prevalence among elderly living in kg. Londang, Masjid Tanah, Malacca - Nuramnani, Binti Shahrin (Universiti Malaysia Sarawak, (UNIMAS), 2012)
A cross - sectional design has been used as the respondents were examined at one point of time by assessing the prevalence of fall among the elderly in Kampong Londang, Masjid Tanah, Malacca. In addition, the study also examine the differences between the prevalence of falls with age, gender, marital status, educational level, living arrangement, medical condition or diseases, and functional. A total of sixty respondents ranging in age from 60 to 101 years were selected using a simple random method from the list of villagers given by the village head. The respondents were interviewed via face-to-face approached using structured questionnaire as a survey tool. The findings showed that the mean age of the respondents was 70.17 years. Visions problems (73.3%) were the commonest medical condition or diseases reported by the respondents, followed by hypertension (66.7%), heart diseases (51.7%), diabetes mellitus (50.0%), hearing problems (11.7%), arthritis (6.7%), and stroke (3.3%). Majority of the respondents reported having more than one medical condition or diseases and had at least once incidence of fall during the previous one r' year. Further findings indicated that 73.3% of the respondents were independent and had experience of fall at least once. The other 10 respondents (16.7%) required assistance from others in performing at least one of the activities of daily living. The findings from this study provide information to primary health care personnel to plan appropriate intervention program. The purpose of the intervention program is to decrease the prevalence of falls and associated risk factors that influences the functional status, in enhancing the quality of life among elderly through health education.